Kajian Literatur: Etnomedisin sebagai Analgesik di Indonesia - Mahacita Andanalusia; Neneng Rachmalia Izzatul Mukhlishah (Journal Syifa Sciences and Clinical Research, 2023)
Ethnomedicine has a major role in the development of new drugs. Based on ethnomedicine studies, it is known that some plants’ biological activity has potential as a therapy. One of its activities is as an analgesic, which can help to deal with frequent pain incidents in the world. The purpose of this literature review was to collect information on the use of ethnomedicine as an analgesic in several regions in Indonesia. The method used was narrative review using the Google Scholar database with publication limits from 2019 to 2023. There were nine studies that meet the criteria and represent the western, central and eastern parts of Indonesia. A total of four studies show that Zingiber officinale is used as an analgesic with UV 0.02-1.0. Three studies show Alpinia galanga and Piper betle are used as analgesic with UV 0.4-1.77 and 0.06-1.20, respectively. Two studies show that Oriza sativa and Curcuma longa are used by the local people as analgesics with a UV of 0.04-1.40 and 0.13-0.45, respectively. Other plants that have high UV in several regions include Orthosiphon aristatus (0.80); Curcuma viridiflora (4.00); Ficus septica (0.43), and Emelia ribes (0.60) Based on the results, it is known that Zingiber officinale, Alpinia galanga, Piper betle, Oriza sativa, and Curcuma longa are the plants most widely used as analgesics in several regions in Indonesia. This literature review can be used as a consideration in finding analgesic support therapy using ethnomedicine.